Uczeń z doświadczeniem migracji na lekcji języka angielskiego: wyzwania i rozwiązania - Rokita-Jaśkow, Joanna (Neofilolog, 2022)
The increasing number of migrant learners in Polish schools poses a new challenge not only for teachers of the language of school education, i.e. Polish, but also for teachers of other subjects, including English. Depending on the migrant learner’s country of origin, English may be his/her foreign, third (or additional) or even first language. This situation increases the heterogeneity of the language group and raises new challenges, which according to Ruiz’s (1984) conceptualization could be approached by the teacher either as a threat to the monolingual policy in the classroom, or as a resource that has the potential to enrich foreign language lessons by developing plurilingual and intercultural competences. On the basis of available research (Rokita-Jaśkow, 2019, 2021), the article presents the challenges teachers face along with suggestions for teaching solutions.